Effect of water on the retention on diol and amide columns in hydrophilic interaction liquid chromatography - Jandera, Pavel; Janás, Petr; Škeříková, Veronika; Urban, Jiří (Wiley-VCH, 2017)
The amount of water adsorbed on polar columns plays important role in hydrophilic interaction liquid chromatography. It may strongly differ for the individual types of polar columns used in this separation mode. We measured adsorption isotherms of water on an amide and three diol-bonded stationary phases that differ in the chemistry of the bonded ligands and properties of the silica gel support. We studied the effects of the adsorbed water on the retention of aromatic carboxylic acids, flavonoids, benzoic acid derivatives, nucleic bases, and nucleosides in aqueous-acetonitrile mobile phases over the full composition range. The graphs of the retention factors versus the volume fraction of water in mobile phase show "U-profile" characteristic of a dual hydrophilic interaction-reversed phase retention mechanism. The minimum on the graph that marks the changing retention mechanism depends on the amount of adsorbed water. The linear solvation energy relationship model suggests that the retention in the hydrophilic interaction liquid chromatography mode is controlled mainly by proton-donor interactions in the stationary phase, depending on the column type. Finally, the accuracy of hydrophilic interaction liquid chromatography gradient prediction improves for columns that show a high water adsorption.
Vliv vody na retenci na diolové a amidové koloně v chromatografii hydrofilních interakcí
Keywords: amide-bonded phases; diol-bonded phases; dual retention mechanism; hydrophilic interaction chromatography; water adsorption on columns; amidová stacionární fáze; diolová stacionární fáze; duální mechanismus retence; chromatografie hydrofilních interakcí; adsorbovaná voda